Analysis of the Effect of Green Financing, Green Investment, Green Marketing on Green Financing Sustainbility With Top Management Support as a Mediation Variable - Palupi Patmasari; Muhammad Iqbal Fasa; Adib Fachri (Penerbit Hellow Pustaka, 2026)
The accelerating global climate crisis has forced the banking sector to transform conventional business models into more sustainable entities. This research aims to analyze the influence of Green Financing, Green Investment, and Green Marketing on Green Financing Sustainability, with Top Management Support serving as a mediating variable. Utilizing a Systematic Literature Review (SLR) approach, this study synthesizes 25 reputable international journals published between 2021 and 2026 to map the dynamics of green strategies within the financial sector. The analysis reveals that Green Financing and Green Investment contribute significantly to mitigating systemic risks and enhancing operational efficiency through capital allocation in low-carbon sectors. Meanwhile, Green Marketing plays a crucial role in building legitimacy and consumer trust, which are key to the stability of third-party funds. A central finding of this research confirms the vital role of Top Management Support as a mediator that transforms strategic vision into measurable operational actions. Without executive-level commitment, green initiatives tend to become mere administrative costs without a tangible impact on sustainability. This study recommends stricter emission reporting standardization from regulators and the internalisation of ESG values by banking practitioners to ensure institutional resilience in the future.